2005
DOI: 10.1089/clo.2005.7.289
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Maternal-Fetal Interaction in Day-30 Bovine Pregnancies Derived from Nuclear Transfer

Abstract: Embryonic mortality and abnormal placental morphology have been reported by most researchers studying nuclear transfer (NT), and it now is accepted that placental anomalies and poor development of cloned embryos are related. As early as day 50 of gestation, cloned bovine concepti exhibit poor structural organization of the developing placentomes. These experiments were designed to identify alterations in maternal-fetal interactions during establishment of the placentas of NT-derived embryos at day 30 of gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…In this model, blastocysts hatch normally but fail to survive or elongate. This peri-implantation defect in ovine uterine gland knockout ewes may be due to the absence of endometrial glands or, alternatively, to the lack of certain epithelial adhesion molecules or the inability of the endometrium to respond to signals from the conceptus (Gray et al, 2000(Gray et al, , 2001(Gray et al, , 2002Spencer et al, 2004;Hoffert et al, 2005;Arnold et al, 2006). Moreover, the success of endometrial gland morphogenesis in neonatal pigs also determines, in part, the embryotrophic and functional capacity of the adult uterus (Bartol et al, 1993(Bartol et al, , 1999Spencer and Bazer, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, blastocysts hatch normally but fail to survive or elongate. This peri-implantation defect in ovine uterine gland knockout ewes may be due to the absence of endometrial glands or, alternatively, to the lack of certain epithelial adhesion molecules or the inability of the endometrium to respond to signals from the conceptus (Gray et al, 2000(Gray et al, , 2001(Gray et al, , 2002Spencer et al, 2004;Hoffert et al, 2005;Arnold et al, 2006). Moreover, the success of endometrial gland morphogenesis in neonatal pigs also determines, in part, the embryotrophic and functional capacity of the adult uterus (Bartol et al, 1993(Bartol et al, , 1999Spencer and Bazer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that survival and elongation are directly related to the degree of glandular development (Gray et al, 2000(Gray et al, , 2001(Gray et al, , 2002Hoffert et al, 2005;Arnold et al, 2006;Burton et al, 2007), developmental arrest during the first trimester in scNT clones may be caused by glandular dysfunction due to a hypoinvasive/hypomigratory phenotype of extravillous trophoblast cells.…”
Section: Down-regulation Of Angiogenic-related Gene Expression In Thementioning
confidence: 99%
“…The placental BNC population in clone pregnancies during early to mid-gestation (days 30-150) has been analyzed by several investigators, with results ranging from fewer (Hashizume et al 2002, Arnold et al 2006 or similar (Hoffert et al 2005) to more ) compared with pregnancies with in vivo-and in vitro-derived embryos. The present study showed that the BNC population at full term was similar in clone and control pregnancies, so it can be surmised that increased SULT1E1 mRNA abundance in clone placenta was due to increased transcription of the gene and/or increased proportion of SULT1E1 producing BNC.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that Dkk-1 is also essential for the differentiation of BNCs before migration and invasion, as suggested by Peng et al [20], or it may subsequently serve, to control the numbers of BNCs present in the placentome. Although the percentage of BNCs within the Day 30 bovine trophoblast was similar in SCNT and IVF derived pregnancies [35] it has been reported that the percentage of BNCs in Days 50, 100 and 150 placentomes was greater in SCNT than AI or IVP [36].Dkk-1 acts as an antagonist in the Wnt pathway. The Wnt family of signalling molecules is important during human placentation for labyrinth development [37] and is essential in the process of implantation of the mouse blastocyst [38].…”
mentioning
confidence: 86%